Evaluation of the Efficacy of Epiduroscopic Laser Neural Discectomy in Lumbar Disc Herniations: Retrospective Analysis of 163 Cases- Evaluation of the Efficacy of ELND - Ali Metin Ülgen; Serbülent Gökhan Beyaz; Mustafa Erkan Inanmaz; Fatih Şahin (Pain Research and Management)
Background. Epiduroscopy, or spinal endoscopy, is the visualisation of the epidural space using a percutaneous and minimally invasive imaging fiberoptic device. Recently, as a result of some studies, it has been reported that laser therapy with epiduroscopic laser neural discectomy (ELND) was applied during multiple lesions. Methods. In this study, ELND performed between January 2012 and July 2016 at the Algology Clinic of the Department of Anesthesiology and Reanimation, Sakarya University Training and Research Hospital, was examined retrospectively. The Oswestry Disability Index (ODI) and Visual Analogue Scale (VAS) scores were recorded preoperatively, as well as after 2 weeks and 2, 6, and 12 months after the ELND. Results. According to the preoperative VAS and ODI scores, the decrease in postoperative 2nd week, 2nd, 6th, and 12th month VAS and ODI scores was significant p=0.001. Similarly, according to the postoperative 2nd week VAS and ODI scores, decrease in postoperative 6th and 12th VAS and ODI scores was significant p=0.001. Conclusions. As a result, ELND with Holmium: YAG laser, which is a new technique in patients with lumbar disc herniated low back and/or leg pain, can reduce VAS and ODI scores from 2 weeks without any complications that open surgery can bring with it. We believe that it is a useful and advanced technique in treatment of lumbar disc herniation and has low complication rates that provides maximum efficacy from the first year.